Why Do Different Countries Use Different Currencies? - Kocherlakota, Narayana (IMF Working Papers; Working Paper ;, 1998)
During long periods of history, countries have pegged their currencies to an international standard (such as gold or the U.S. dollar), severely restricting their ability to create money and affect output, prices, or government revenue. Nevertheless, countries generally have maintained their own currencies. The paper presents a model where agents have heterogeneous preferences-that are private information-over goods of different national origin. In this environment, it may be optimal for countries to have different currencies; we also identify conditions where separate national currencies do not expand the set of optimal allocations. Implications for a currency union in Europe are discussed.